2011
DOI: 10.1002/pssb.201046508
|View full text |Cite
|
Sign up to set email alerts
|

High pressure phase transitions in Mg1–xCaxO: Theory

Abstract: We have analysed a B1 ! B2 structural phase transitions in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 46 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Twinning formation is common in crystalline films, with 180°mirror images having almost identical formation energy as shown in the Mg 0.72 Ca 0.28 O left-right symmetric diffraction pattern [38,39]. Moreover, from the diffraction pattern, the zone axis of the SiC substrate in these TEM images is 11 [40]. But the TEM diffraction pattern clearly showed that there is no phase other than rock salt and also no phase separation is observed.…”
Section: Epitaxial Growth Of Mg X Ca 1−x O On Sicmentioning
confidence: 68%
“…Twinning formation is common in crystalline films, with 180°mirror images having almost identical formation energy as shown in the Mg 0.72 Ca 0.28 O left-right symmetric diffraction pattern [38,39]. Moreover, from the diffraction pattern, the zone axis of the SiC substrate in these TEM images is 11 [40]. But the TEM diffraction pattern clearly showed that there is no phase other than rock salt and also no phase separation is observed.…”
Section: Epitaxial Growth Of Mg X Ca 1−x O On Sicmentioning
confidence: 68%
“…26 In the case of mixed phase oxides there is experimental evidence that these exist at high temperature 27 and as a result of molecular beam epitaxy. [28][29][30] Some theoretical work investigating thermodynamic stability has been reported at high pressure and temperature 31 and using the local density approximation (LDA). 32 In this study we directly investigate the composition of dolomitic lime, conrming the degree of phase-separation and defect concentration following decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…26 In the case of mixed phase oxides there is experimental evidence that these exist at high temperature 27 and as a result of molecular beam epitaxy. [28][29][30] Some theoretical work investigating thermodynamic stability has been reported at high pressure and temperature 31 and using the local density approximation (LDA).…”
mentioning
confidence: 99%
“…Stolbov and Cohen[10] have studied the electronic structure for equilibrium MgO-CaO. Miloua et al[11] have calculated the electronic properties of Besides, A. Srivastava et al[12] calculated phase translations in…”
mentioning
confidence: 99%